2007
DOI: 10.1152/ajpheart.01102.2006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced activation of cardiac sympathetic nerve triggers cardioprotection via redox-sensitive activation of eNOS and upregulation of iNOS

Abstract: We investigated the mechanism of exercise-induced late cardioprotection against ischemia-reperfusion (I/R) injury. C57BL/6 mice received treadmill exercise (60 min/day) for 7 days at a work rate of 60-70% maximal oxygen uptake. Exercise transiently increased oxidative stress and activated endothelial isoform of nitric oxide synthase (eNOS) during exercise and increased expression of inducible isoform of NOS (iNOS) in the heart after 7 days of exercise. The mice were subjected to regional ischemia by 30 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 43 publications
1
40
1
2
Order By: Relevance
“…Our data indicate that elevated ROS underlies the late preconditioning effect of sulindac and that downstream PKC activation is also necessary for the molecular changes and protective responses. There is an extensive body of work implicating ROS dependent mechanisms in the triggering of delayed preconditioning by ischemia, exercise or other preconditioning stimuli (33)(34)(35)(36)(37). Following the trigger the next step in late preconditioning requires signaling through pathways that involve key protective kinases including PKC epsilon and PKC epsilon/Src containing modules (38,33).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that elevated ROS underlies the late preconditioning effect of sulindac and that downstream PKC activation is also necessary for the molecular changes and protective responses. There is an extensive body of work implicating ROS dependent mechanisms in the triggering of delayed preconditioning by ischemia, exercise or other preconditioning stimuli (33)(34)(35)(36)(37). Following the trigger the next step in late preconditioning requires signaling through pathways that involve key protective kinases including PKC epsilon and PKC epsilon/Src containing modules (38,33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have reported an increase in the expression of superoxide dismutase (7), catalase (44), and heat-shock proteins (HSPs) (44,48) after exercise. Others reported that exercise increases the expression and activity of endothelial NO synthase (eNOS), resulting in an increase in NO levels (1). Still others report that exercise activates ATP-sensitive potassium channels (sarcolemmal and mitochondrial) in cardiovascular tissues (6,57).…”
Section: Putative Cardioprotective Mechanisms Of Exercisementioning
confidence: 99%
“…Evidence has been presented that exercise-mediated protection involves PI3K and Akt (243), may require nitric oxide synthase (6), and involves GPCRs that also trigger Precon (45). The question arises then as to how and why exercise retains efficacy with age or disease whereas Precon responses involving common signal elements fail?…”
Section: Restoration Of Conventional Protectionmentioning
confidence: 99%